DINAMIKA KETERWAKILAN PEREMPUAN DI DPRD PROVINSI NTB TAHUN 2024 - Nabilah Bahri; Siti Atika Rahmi; Yudhi Lestanata; Ayatullah Hadi (Nusantara Hasana Journal, 2025)
This study is motivated by the low representation of women in legislative institutions, particularly in the Regional House of Representatives (DPRD) of West Nusa Tenggara Province, which reached only 1.54% in the 2019 election. The research aims to analyze the opportunities and challenges faced by women in running for legislative office in the 2024 election. A descriptive qualitative method was used, with data collected through interviews, observations, and documentation involving key informants. The results show that despite affirmative policies such as the 30% quota for women being legally mandated, implementation remains hindered by factors such as patriarchal culture, limited access to education and political information, and insufficient party support. Nevertheless, growing gender awareness, central government policies, and increased involvement of women's organizations present greater opportunities for female representation in parliament. In conclusion, increasing both the quantity and quality of women's representation requires continuous efforts from various stakeholders, including the government, political parties, and civil society, to establish a more inclusive and gender-eq uitable political system